2010
DOI: 10.1007/s00442-010-1713-2
|View full text |Cite
|
Sign up to set email alerts
|

The cost of maturing early in a solitary carnivore

Abstract: Central to the theory of life history evolution is the existence of trade-offs between different traits, such as the trade-off between early maturity and an extended period of body growth. Based on analysis of the reproductive tracts of harvested Eurasian lynx (Lynx lynx) females in Norway, we find that females that mature early are generally heavier than those that postpone maturation. A higher proportion of 1.5-year-old females showed signs of ovulation in areas with high prey density, where they were also h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…In general the breeding proportion was highest in the southernmost study population (Bergslagen), and lowest in the northernmost population (Sarek), with both the Norwegian populations showing intermediate values. Supporting these findings, we have previously found that the proportion of 1.5-year-old females that ovulate (i.e., that are sexually mature) was generally lower in the northernmost areas (Nilsen et al 2010). Consequently, on a broad scale the patterns might indicate a slower life cycle in more extreme northern environments.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In general the breeding proportion was highest in the southernmost study population (Bergslagen), and lowest in the northernmost population (Sarek), with both the Norwegian populations showing intermediate values. Supporting these findings, we have previously found that the proportion of 1.5-year-old females that ovulate (i.e., that are sexually mature) was generally lower in the northernmost areas (Nilsen et al 2010). Consequently, on a broad scale the patterns might indicate a slower life cycle in more extreme northern environments.…”
Section: Discussionsupporting
confidence: 61%
“…While there was a clear difference between females that were 2 years old and those that were older in the proportion that gave birth, litter sizes did not differ between these age classes, indicating that females that mature early invest relatively heavily in their first litter (see also Nilsen et al 2010). This might be somewhat surprising given the potentially high costs of reproduction at low age in carnivores (Proaktor et al 2007).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In response to this, separate female quotas in the lynx harvest have been allocated since the late 1990s in Norway. Although considerable effort has been spent in studying lynx ecology in Norway (Andrèn et al 2006;Nilsen et al 2010;Nilsen et al 2009;Odden et al 2006), so far little is known about the magnitude and composition of the harvest, and even less is known about the bag composition in relation to the standing population structure (Saether et al 2010).…”
Section: Introductionmentioning
confidence: 99%